Keragaman Genetik Sekuen Gen ATP Synthase FO Subunit 6 (ATP6) Monyet Hantu (Tarsius) Indonesia (GENETIC DIVERSITY STUDY OF ATP6 GENE SEQUENCES OF TARSIERS FROM INDONESIA) - Widayanti, Rini; Handayani, Niken Satuti Nur; Wijayanto, Hery (Jurnal Veteriner; Vol 13 No 4 (2012), 2013)
In a conservation effort, the identification of Tarsier species, on the bases of the morphological andmolecular characteristic is necessary. Up to now, the identification of the animals were based on themorphology and vocalizations, which is extremely difficult to identify each, tarsier species. The objective ofthis research was to study the genetic diversity on ATP6 gene of Tarsius sp. Based on sequencing of PCRproduct using primer ATP6F and ATP6R with 681 nts. PCR product. The sequence of ATP6 fragmentswere aligned with other primates from Gene bank with aid of software Clustal W, and were analyzed usingMEGA program version 4.0. Three different nucleotide sites were found (nucleotide no. 288, 321 and 367).The genetic distance based on nucleotide ATP6 sequence calculated using Kimura 2-parameter modelindicated that the smallest genetic distance 0%, biggest 0.8% and average 0, 2%. The phylogenetic treeusing neighbor joining method based on the sequence of nucleotide ATP6 gene could not be used todifferentiate among T. Dianae (from Central Sulawesi), T. Spectrum (from North Sulawesi), T. bancanus(from lampung, South Sumatera) and T.bancanus from West Kalimantan.
Keywords: Tarsier sp., ATP6 gene, nucleotide, mt-DNA sequences